2021
DOI: 10.3390/vaccines9070801
|View full text |Cite
|
Sign up to set email alerts
|

Timely Birth Dose Vaccine to Prevent Vertical Transmission of Hepatitis B: A Single Center Experience on the Road to the WHO Elimination Goals in Italy

Abstract: Italy was one of the first industrialized countries to implement a program of routine vaccination against hepatitis B virus (HBV) infection. However, currently, no HBV vaccine is administered at birth if the screened mother is HBsAg negative, whilst babies born to HBsAg positive mothers are given vaccine and hepatitis B immunoglobulin, within 12–24 post-delivery hours. A single center retrospective analysis of policies and practices to prevent mother-to-child transmission of HBV was carried out, to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…and men who have sex with men [ 32 ], for whom the HBV vaccination is strongly recommended and free of charge [ 8 , 33 , 34 , 35 ]. Moreover, Pinon et al found a not-always-appropriate surveillance of HBsAg-positive women during pregnancy [ 36 ]. Despite Italy providing HBV screening to pregnant women, along with timely immune-prophylaxis and hepatitis-B vaccination at birth to newborns of seropositive women [ 37 ], health authorities should consider the possibility of investing more resources also in the screening of pregnant women, in order to prevent HBV vertical-transmission.…”
Section: Discussionmentioning
confidence: 99%
“…and men who have sex with men [ 32 ], for whom the HBV vaccination is strongly recommended and free of charge [ 8 , 33 , 34 , 35 ]. Moreover, Pinon et al found a not-always-appropriate surveillance of HBsAg-positive women during pregnancy [ 36 ]. Despite Italy providing HBV screening to pregnant women, along with timely immune-prophylaxis and hepatitis-B vaccination at birth to newborns of seropositive women [ 37 ], health authorities should consider the possibility of investing more resources also in the screening of pregnant women, in order to prevent HBV vertical-transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the prevention strategies at birth highlighted that 91% of the departments provide for infants born to HBsAg positive mothers HBV vaccine plus HBIG within 12 hours from birth, according to guidelines (9,(11)(12)(13). Nevertheless, only 61% of 235 babies born to HBV positive mothers between 2015 and 2019 at the Italian hospital with the highest number of deliveries per year received immunoprophylaxis within 12 hours from birth (20).…”
Section: Discussionmentioning
confidence: 99%